Exercise preconditioning protects against doxorubicin-induced cardiac dysfunction - Hydock, D. S.; Lien, C.-Y.; Schneider, C. M.; Hayward, R. (Medicine & Science in Sports & Exercise, 2008)
The clinical use of the chemotherapeutic drug doxorubicin (DOX) is limited due to a dose-dependent cardiotoxicity. Evidence is mounting that exercise protects against DOX-related cardiac dysfunction, and as such, it may be possible that prior endurance training promotes defense against DOX cardiotoxicity.